Being a Sensible Woman: Hypertextuality in Grimm’s Fairy Tale and Juliet Marillier’s Wildwood Dancing - Alberta Natasia Adji (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
The re-writing of a fairy tale caters for characters, settings and values that have undergone changes, be it explicit or implicit. In Juliet Marillier’s Wildwood Dancing, the main female character Jena is transformed from the passive and obedient Twelfth/Youngest Princess of Grimm’s The Worn-Out Dancing Shoes into a brave and sensible figure. She challenges the oppression of patriarchal rules by taking control of her household in her father’s absence, securing her four sisters’ welfare, and keeping secret of their nocturnal dancing trips in the Other Kingdom despite being threatened by her domineering male cousin. In this way, Gerard Genette’s Hypertextuality strives to investigate the underlying patterns manifested in both literary works by applying the Re-vision element. Through it, Jena’s and the Twelfth/Youngest Princess’ sensibility trait and the socio-cultural settings surrounding them are highlighted in order to determine the importance of the overall hypertextuality process that takes place between the two. Later, Jena emerges as the more influential heroine than her predecessor character because she does not stop struggling to be regarded as an independent young woman who can always give advice and make decisions for her family affairs sensibly. Also, it is eventually proven that sensibility is indeed a strong weapon to be possessed by women in order to empower themselves against the conventions of a patriarchal world.